Skeletal disproportion in girls with Turner syndrome and longitudinal change with growth‐promoting therapy. (7th February 2021) - McVey, Lindsey C.; Fletcher, Alexander; Murtaza, Mohammed; Donaldson, Malcolm; Wong, Sze Choong; Mason, Avril
Abstract: Objective: Short stature in Turner syndrome (TS) may be accompanied by skeletal disproportion. This retrospective study investigates growth and disproportion from early childhood to adult height. Study design: Data were collected from 59 girls prior to growth hormone (rhGH) treatment and in 30 girls followed up longitudinally. Standard deviation scores (SDS) for height (Ht), sitting height (SH) and sub‐ischial leg length (LL) were compared and a disproportion score (SH SDS – LL SDS) calculated. Results: In 59 girls, mean (SD) age 6.6 (2.1) years prior to rhGH treatment, LL SDS of −3.4 (1.1) was significantly lower than SH SDS of −1.2 (0.8) [ p  < .001]. In girls with Ht SDS < −2.0, disproportion score was > +2.0 in 27 (63%), cf eight (50%) with Ht SDS ≥ −2.0. For the longitudinal analysis, skeletal disproportion prior to rhGH was +2.4 (1.1) and +1.7 (1.0) on rhGH but prior to introduction of oestrogen [ p  < .001]. Disproportion at adult height was +1.1 (0.8), which was less marked than at the earlier time points [ p  < .001 for both comparisons]. Change in disproportion SDS over the first two years of rhGH predicted overall change in disproportion from baseline to adult height [R 2 51.7%, p  < .001]. Conclusion: TS is associated with skeletal disproportion, which is more severe in the shortest girls and present in only half of those with milder degrees of short stature. Growth‐promoting therapy may improve disproportion during both the childhood and pubertal phases of growth. Change in disproportion status two years after starting rhGH helps predict disproportion at adult height.